Assessing the Influence of Strategic Tillage on Crop Yields and Soil Properties in Dryland No-Tillage Systems - Mikaela A. Lawrence; Augustine K. Obour; John D. Holman; Logan M. Simon; Lucas A. Haag; Kraig L. Roozeboom (Kansas Agricultural Experiment Station Research Reports, 2023)
Implementing strategic tillage (ST) in otherwise long-term no-till (NT) systems could control herbicide resistant weeds and increase profitability of crop production in semi-arid dryland cropping systems. For the purpose of this study, ST is defined as a single tillage event (once every 6-10 years) in an otherwise NT system to reduce density of herbicide tolerant grass weeds. However, there is little information on the long-term (>5 years) effects of ST on soil health parameters and crop yields. This study used long-term tillage and crop rotation plots established in 1976 at the Kansas State University Agriculture Research Center in Hays, KS. Treatments include three rotations: continuous wheat (WW), wheat-sorghum-fallow (WSF), and wheat-fallow (WF); and two tillage regimes: no-till (NT) and reduced tillage (RT). In 2016, a new tillage treatment, ST, was added to control herbicide resistant (HR) grass weeds and to mix soil to reduce nutrient and pH stratification. Soil samples were collected following wheat harvest in 2022 to investigate soil properties after 5 years of ST. Results of the 2022 sampling showed rotation and tillage had no significant effect (P>0.05) on bulk density. However, bulk density was least in the 0- to-2-inch soil depth compared to the 2- to 6-inch and 6- to 12-inch depths, with values of 1.16, 1.44, and 1.39 g/cm3, respectively. Soil organic carbon (SOC) was greatest in the 0- to 2-inch soil depth. The SOC concentration in soils under NT was not different compared to ST, whereas soils under RT had 8% less SOC than NT. Wind-erodible fraction (WEF) was not different among tillage treatments. Tillage treatments had a significant effect on mean weight diameter (MWD), with NT having the highest MWD followed by ST. Winter wheat yield was greatest in RT across the crop rotations. Strategic tillage increased wheat yields in WW compared to NT. Crop rotation, tillage intensity, and depth were all important with pH because pH was highest in WW rotation, RT tillage, and the 6- to 12-inch soil depth. Phosphorus concentrations were highest in WW and the 0- to 2-inch soil depth. Potassium had the greatest concentrations in RT and the 0- to 2-inch soil depth. Grain sorghum yield was not different between NT and ST, but yields for both were greater than RT. Overall, ST had no negative effect on soil properties or crop yield and can be a mitigation option to control herbicide resistant weeds and increase profitability of dryland crop production.
Keywords: no-tillage; strategic tillage; soil properties